Association between hospital volume and outcomes in ovarian cancer: a systematic review - Luo, Qing; Wang, Yan; Zhang, Xiaoyun (Frontiers in Surgery, 2025)
BackgroundHospital surgical volume has been proposed as a determinant of ovarian cancer (OC) outcomes, but findings remain inconsistent.ObjectiveTo systematically assess the association between hospital volume and outcomes in OC patients.MethodsA systematic search of PubMed, Embase, and Cochrane Library was conducted through January 2025. Fifteen observational studies involving over 100,000 OC patients were included and qualitatively synthesized.ResultsThirteen of fifteen studies demonstrated that treatment in high-volume hospitals was significantly associated with improved overall survival (OS). Reported benefits included a 5-year OS increase from 22.3% to 55.0%, and up to 3% OS gain per 20 additional surgeries per year. High-volume centers also showed lower perioperative and 90-day mortality (e.g., 0.9% vs. 2.5%), and reduced failure-to-rescue rates. Two studies reported longer progression-free survival (PFS) in high-volume settings. Surgical quality indicators—such as complete cytoreduction and lymphadenectomy—were consistently higher in high-volume hospitals. Despite slightly higher complication rates, these centers had shorter hospital stays and better complication management.ConclusionsHigher hospital surgical volume is associated with better survival, lower mortality, and superior surgical quality in OC patients. Centralization of OC care may optimize outcomes and should be considered in policy planning.